Gamified hidden-assessment platform for diagnosing ICT competences and supporting career guidance among Kazakhstani high-school students - Tokzhigitova, Nurgul; Jarassova, Gulzhan; Tokzhigitova, Ainur; Ospanova, Nazira; Baizhumanov, Saduakas (Frontiers in Education, 2025)
Digitization is reshaping Kazakhstan's labor market; yet school-based career guidance still relies on paper inventories that fail to uncover students' latent interests in emerging technology domains. We developed Game for Career Guidance (GCG). This bilingual (web-based) platform combines gamification with hidden assessment to profile upper-secondary pupils' competences in programming, cyber-security, web development, graphics/UX, and computer architecture. A 6-week field trial involved 1,865 grade-11 learners from 45 state schools in Pavlodar. Gameplay logs captured unobtrusive event traces, which were converted to Rasch-weighted mastery scores; post-session surveys measured motivation, usability, and state anxiety. Eighty-three percent of participants reached at least medium mastery in three or more domains, and 92 % completed the tutorial and entered formal play. Mean Intrinsic Motivation Inventory (5.6/7) and System Usability Scale (SUS) (76/100) scores indicated high engagement and usability, while state-anxiety remained low (1.9/5). Hierarchical models showed that flow significantly predicted mastery after controlling for prior GPA. Qualitative feedback echoed these findings and emphasized the value of authentic micro-tasks and a seamless Kazakh–Russian interface. The results demonstrate that gamified hidden assessment can motivate learners and deliver fine-grained evidence for counselors without additional testing time. The open-source architecture offers a readily scalable blueprint for modernizing career guidance in other rapidly digitizing educational systems.